KONDISI EKONOMI MASYARAKAT PETAMBAK PASCA IMPLEMENTASI KEBIJAKAN MINAPOLITAN DI KABUPATEN GRESIK - Rozikin, Mochammad (Fakultas Ekonomi Universitas Wisnuwardhana, 2020)
Abstract: Gresik Regency has a large potential of capture fisheries and cultivation so that the Ministry of Maritime Affairs and Fisheries is designated as a pilot of the Minapolitian project. This study aims to determine the impact of the implementation of the Minapolitan policy on the economic conditions of pond communities in Gresik Regency. The method used is qualitative descriptive with a focus of research: 1) efforts made by the government in implementing the Minapolitan policy; and 2) economic conditions of the pond community after the implementation of the Minapolitian policy. The results showed that the government had tried to improve infrastructure (infra-structure) around the ponds to make it easier for farm communities to run aquaculture activities, but had not been able to support the needs of production facilities. As for the economic conditions of the community, it has not significantly increased the income of the community and opened employment opportunities for the youth. Keywords: Economic Condition, Farmers Community, Post-Implementation of Minapolitan Policy